SETTLEMENT PATTERN OF THE VILLAGE OF DAYEUH LUHUR, SUMEDANG - Wijaya, Karto; Permana, Asep Yudi (Universitas Pendidikan Indonesia, 2020)
The village of Dayeuh Luhur, Ganeas District, Sumedang is a village located on a mountain. This village has a close relationship with the history of the Kingdom of Sumedang Larang, which at that time was in conflict with the Sultanate of Cirebon. King Sumedang Larang ordered to move the royal government to a safer place, namely Mount Rengganis (now called Desa Dayeuh Luhur). Over time, this place developed into a settlement that was visited by tourists. This village has a pilgrimage destination which is the tomb of King Sumedang Larang and other royal heritage sites. The purpose of this study was to determine the characteristics of mountain settlement patterns and environmental forming factors in the village of Dayeuh Luhur. The research method used is a qualitative descriptive approach. The results of this study can also be a good reference for policy makers and the preservation of living culture, architecture and ordinary people.Â Keywords â€“ Settlement patterns, mountainous areas, pilgrimage tours.